CRITICAL REFLECTIONS OF A CHEMISTRY TEACHER EDUCATOR IN REVEALING TEACHING IDENTITY: A CRITICAL AUTOETHNOGRAPHY RESEARCH - Yuli Rahmawati; Peter C Taylor; Rekha K Koul (Jurnal Riset Pendidikan Kimia (JRPK), 2013)
This article focuses on critical reflections on my teaching identity when I engaged as a co-teacher with three science teachers and their students from different social and cultural backgrounds. I am a university based chemistry teacher educator from Indonesia who worked in a 3-year longitudinal co-teaching project in lower secondary schools in Western Australia. As the research involved critical reflection on my own professional praxis, I adopted a multi-paradigmatic research approach with critical auto/ethnography as the research methodology. Over time, critical reflection enabled me to develop difference awareness, empathy and rapport, sharing of control and power, mutual understanding and negotiation. However, I found myself struggling to engage deeply with the science teachers and their students, due in part to socio-cultural factors. In this article, I investigate my autobiographical self as a science teacher educator facing the dilemma of aspiring to become increasingly empowered whilst simultaneously being controlled by external socio-cultural forces. As I worked with the 3 science teachers I found within their characters a mirror of my own history as a science teacher. I came to realise the power of meaning making for students’ learning and also that in my own teaching history I had ignored it when the power of the technical interest strongly controlled the science classroom. The journey of working closely with the three science teachers invoked in me continuous reflection on my own evolving teaching identity as a science educator who is committed to transformative learning theory, who has faith in constructivism as a pedagogical referent, who envisions better teacher-student relationships, and who is trying to establish the wisdom of dialectical thinking; a set of beliefs that I hope will help me to stay on the pathway of increasing empowerment for better education. Key Words: Co-teaching, teaching identity, auto/ethnography, transformative learning